Effects of Maternal Anemia on Neonatal Outcome - Adhikari, Jyoti; Belbase, Mohan; Rijal, Shikha (Journal of Nepalgunj Medical College, 2022)
Introduction: Anemia is one of the most prevalent nutritional deficiency problem affecting pregnant women. It is defined by World Health Organization as hemoglobin (Hb) level of less than 11 g/dl. Hemoglobin level of 9.0- 10.9 g/dl is mild, 7.0-8.9 g/dl is moderate and less than 7 g/dl is severe anemia respectively. Maternal anemia in pregnancy is commonly considered as a risk factor for poor pregnancy outcome and can result in complications that threaten the life of both mother and fetus. Aims: To find out neonatal outcome delivered to anemic mothers. Methods: A prospective case control study was carried out among 75 newborns delivered to pregnant women with hemoglobin below 10.9g/dL. Another 75 newborns were taken delivered at the same time, matched age and sex wise as a control group to mothers whose hemoglobin was more than 11g/dl. Results: Out of total 75 cases 35(46.7%) mothers had mild, 32(42.6%) had moderate and 8(10.7%) had severe anemia respectively. Similarly, the risk of having preterm baby among anemia group was 4.42 times higher than that in control group (p 0.033). The risk of having low birth weight in anemia group was 3.9 times higher than that in control group (p 0.04). The mean of head circumference (HC) among the anemia group was 33.9cm +1.40 (Mean+SD) and among the control group was 34.4cm+1.24(Mean+SD) with a mean difference of 0.5cm (p 0.032). The mean of length among anemia group was 45.3cm+1.97 (Mean+ SD) and among the control group was 46.2cm+1.69 (Mean+ SD) with a mean difference of 0.9 cm (p 0.003). Conclusion: Maternal anemia in pregnancy is associated with increased risk of adverse neonatal outcome. Efforts must be made to reduce the prevalence of anemia especially during pregnancy to reduce neonatal morbidity and mortality.